History, development and future of cancer screening in Australia - Ian N Olver; David Roder (Public Health Research & Practice, 2017)
Introduction: The aim of screening an asymptomatic population for cancer is to achieve better health outcomes, particularly a population survival benefit. Australia has three population screening programs: the National Cervical Screening Program (NCSP), BreastScreen Australia and the National Bowel Cancer Screening Program (NBCSP).